2020
DOI: 10.1016/j.celrep.2020.108465
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic Acid Promotes Endothelial Cell Cycle Early G1 State to Enable Human Hemogenic Endothelial Cell Specification

Abstract: Highlights d A simple and efficient protocol to derive human hemogenic endothelial cells is described d Functional human hemogenic endothelial cells are characterized on a clonal level d Retinoic acid signaling is required for human hemogenic endothelial specification d Cell-cycle state is a critical determinant of human endothelial cell specification

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Coronary artery development is impaired when cell cycle control is disrupted by overexpression of Nr2f2 to promote proliferation in the progenitor endothelial cells coming from the sinus venosus 3 . In addition, we previously found that p27-mediated cell cycle arrest is also required for endothelial cells to undergo hemogenic specification during definitive hematopoiesis 60 , and retinoic acid promotes early G1 arrest in human endothelial cells in vitro to enable hemogenic specification 61 . Thus, regulation of cell cycle state may be required to enable the phenotypic specialization of all endothelial cell subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…Coronary artery development is impaired when cell cycle control is disrupted by overexpression of Nr2f2 to promote proliferation in the progenitor endothelial cells coming from the sinus venosus 3 . In addition, we previously found that p27-mediated cell cycle arrest is also required for endothelial cells to undergo hemogenic specification during definitive hematopoiesis 60 , and retinoic acid promotes early G1 arrest in human endothelial cells in vitro to enable hemogenic specification 61 . Thus, regulation of cell cycle state may be required to enable the phenotypic specialization of all endothelial cell subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, one study found that inhibiting RA led to modest increases in the expression of ASM markers (Chen et al, 2014). However, this previous work cultured explants in the presence of 10% serum, which can significantly alter the concentration of retinol (Engedal et al, 2006) and would also be expected to alter cell proliferation, which can affect RA responsiveness in some tissues (Marcelo et al, 2013;Qiu et al, 2020). Here, we measured the distribution of αSMA protein, which forms the core of the smooth muscle cytoskeletal machinery (Jaslove and Nelson, 2018), and found that inhibiting RA decreases αSMA-positive cells at the tips of epithelial branches.…”
Section: Discussionmentioning
confidence: 94%
“…With regards to cellular proliferation and differentiation, ATRA exerts its influence by promoting the progression of cells through the cell cycle, particularly the G1 phase. This is achieved through the activation of genes supportive of cell division while concurrently suppressing genes associated with cell cycle arrest [131]. Moreover, ATRA signaling contributes significantly to morphogenesis.…”
Section: Growth Cellular Differentiation Morphogenesis and Reproducti...mentioning
confidence: 99%